2022
DOI: 10.1177/00472875221119968
|View full text |Cite
|
Sign up to set email alerts
|

Attribution Theory Revisited: Probing the Link Among Locus of Causality Theory, Destination Social Responsibility, Tourism Experience Types, and Tourist Behavior

Abstract: From a parochial perspective, destination social responsibility (DSR) is crucial in maintaining tourists’ loyalty, trust, and satisfaction. From a broad sense, destination social responsibility could play an essential role as an attribution shifting mechanism inside tourists’ mindsets and differ according to tourism experiences’ nature. To investigate this broad sense, the present study is the first to use locus of causality theory (LOC) to address this issue. By employing a quantitative method, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…To examine the effect of negative reviews, this study adopted attribution theory to analyze how review features influence consumers’ physician selection intention. Past studies have confirmed that online reviews can influence consumer choice through attribution evaluation [ 72 - 74 ]. This study differs from these prior studies as we focused on negative physician reviews and different locus attributions.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the effect of negative reviews, this study adopted attribution theory to analyze how review features influence consumers’ physician selection intention. Past studies have confirmed that online reviews can influence consumer choice through attribution evaluation [ 72 - 74 ]. This study differs from these prior studies as we focused on negative physician reviews and different locus attributions.…”
Section: Discussionmentioning
confidence: 99%
“…Tourism promotion campaigns affect tourists’ travel decision-making (Soliman, 2021). Tourists need to feel that service providers at tourist destinations will cover their needs and preferences before booking their holidays (Saleh, 2023). For example, female tourists seek more information than males related to tourist destinations to enjoy their holidays (Wang et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourists frequently use this hypothesis to explain the reasons behind their experiences of a place, such as why something excellent or unpleasant happened [ 31 ]. One of the most critical aspects of understanding visitor behavior towards CSR programs is the controllability and characteristics of the theory of attribution of stability [ 32 ]. The idea of attribution theory relies on psychological concepts that pinpoint the data individuals rely on to determine whether an event or group of events caused an event.…”
Section: Literature Reviewmentioning
confidence: 99%